The effects of Transcranial Direct Current Stimulation on psychomotor performance of athletes: a systematic review and meta-analysis - Thais Alves-Lobão; Luis Felipe Sarmiento-Rivera; Flavia B. Xavier Vale; Yan Sobral Campos; Fabio Alexis Rincon-Uribe; Rejane Célia de Souza Godinho; Italo Sergio Lopes Campos; Janari da Silva Pedroso; Amauri Junior (Desafio Singular, 2022)
Psychomotor performance is a complex function generated by brain and motor systems integration, measured by accuracy, latency, and movement speed. In sports, to look for ways to improve movements is usual. Also, to utilize Transcranial Direct Current Stimulation (tDCS) as technique of non-invasive stimulation may produce alterations in psychomotor sport skills. We conducted a systematic review including experimental studies with sham or control groups in adults reporting tDCS effects on athletes' psychomotor performance. Cochrane Manual for Systematic Reviews and the statement on systematic reviews and meta-analysis of PRISMA-P (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols) were followed. PsycINFO, PubMed (central), Scopus, Web of Science, Embase, SPORTDiscus, and Cochrane Library databases were searched. Empirical studies published in English, Spanish, and Portuguese from 2009 onwards and whose primary results presented an effective measure of transcranial direct current stimulation in the psychomotor performance of adult athletes were included. The results list 10 articles, 6 of them entered in the meta-analyses. The articles presented a low risk of bias and low publication bias but great dispersion of stimulation areas. PROSPERO register number: PROSPERO RD42020210550